Midterm results of different treatment methods for myocardial bridging in patients after septal myectomy. Issue 2 (1st December 2020) - Wang, Shengwei; Wang, Shuiyun; Lai, Yongqiang; Song, Yunhu; Cui, Hao; Song, Changpeng; Meng, Liukun; Zhu, Changsheng; Wu, Rong; Huang, Xiaohong
Abstract: Background: Myocardial bridging (MB) is commonly treated in patients with hypertrophic cardiomyopathy. However, whether and how MB should be treated in patients with hypertrophic obstructive cardiomyopathy (HOCM) who underwent septal myectomy remain unclear. Methods: A total of 823 adults with HOCM who underwent septal myectomy at the Fuwai Hospital from 2011 to 2017 were retrospectively studied. Results: Overall, 31 events occurred: 24 patients died and 7 had nonfatal myocardial infarction (MI). The 3‐year cumulative event‐free survival of all‐cause death (97.9% vs. 100% vs. 100% vs. 98.4%, p  = .89) and cardiovascular death (98.3% vs. 100% vs. 100% vs. 98.4%, p  = .63) were similar among the four groups (non‐MB, coronary artery bypass grafting [CABG], unroofing, untreated, respectively). However, the 3‐year cumulative event‐free survival of nonfatal MI (100% vs. 97.5% vs. 98.0% vs. 89.9%, p  < .001) and combined endpoints (97.9% vs. 97.5% vs. 98.0% vs. 88.4%, p  = .02) were significantly lowest in untreated MB (non‐MB, CABG, unroofing, untreated, respectively). Cox regression analysis indicated that untreated MB was a significant independent predictor of combined endpoints (hazard ratio: 4.06, 95% confidence interval: 1.60–10.32, p  < .001). Moreover, 49 patients underwent coronary artery computed tomography 1 year after surgery. The patency rate of the saphenous vein graft was significantly higher than that of the left internal mammary artery (13.3% vs. 84.2%, p  < .001). No MB was detected in the unroofing group. Conclusions: Surgical MB treatment could be beneficial and performed safely during septal myectomy. Myocardial unroofing is the recommended treatment for MB, and unroofing when technically possible may be preferable for long‐term outcomes.